The effect of Consumption of Black Sorbean Tempe against Blood Plasma Amino Acid Profiles of Rats - Nurrahman Nurrahman (Fakultas Pertanian Universitas Veteran Bangun Nusantara Sukoharjo, 2017)
Tempe is a food derived from plant materials that have a high-quality protein, easy to digest and low anti-nutritional. This study aims to determine the effect of the consumption of black soybean tempe against blood plasma amino acid profiles of rats. A total of 20 rats were grouped into 5 (five). Rats were placed in individual cages and room temperature (25 - 27oC). Maintained for 30 days of each group were treated with the standard feeding and feed plus black soybean tempe flour (25, 50, 75 and 100% instead of casein). On day 31, as many as 20 rats as much as 1 ml of blood is taken. Obtained blood plasma was separated to be used for the analysis of amino acid profile. The results showed that there were 14 types of amino acids detected in the blood plasma. The highest amino acid was glutamic acid and the lowest was glutamine. Consumption of black soybean tempe increased blood plasma amino acid levels.